Absolute measurements of air shock-layer radiation in the T6 Aluminium Shock Tube - Collen, PL; Glenn, AB; Doherty, LJ; McGilvray, M (American Institute of Aeronautics and Astronautics, 2023)
This paper presents the first experimental measurements of shock-layer radiation from a new high-enthalpy ground-test facility: the T6 Aluminium Shock Tube mode. A dual-channel imaging emission spectroscopy system was used to record spatially and spectrally resolved, absolute radiation data from air shock layers at velocities ranging from 7 to 10km⋅s−1. The presented conditions are designed to provide overlap with other experimental datasets in the literature, from both the NASA Electric Arc Shock Tube and an atmospheric plasma torch. Comparisons with these data (as well as computational tools) was favorable, thereby benchmarking the data from the new shock tube against established sources. The measurements made in this paper also confirm that T6 is now the first European facility capable of performing such superorbital shock-layer radiation studies, thereby providing a new capability to support current and future missions in the solar system.